2019
DOI: 10.7717/peerj.7968
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes and pathways associated with cholangiocarcinoma development based on weighted gene correlation network analysis

Abstract: BackgroundAs the most frequently occurred tumor in biliary tract, cholangiocarcinoma (CCA) is mainly characterized by its late diagnosis and poor outcome. It is therefore urgent to identify specific genes and pathways associated with its progression and prognosis.Materials and MethodsThe differentially expressed genes in The Cancer Genome Atlas were analyzed to build the co-expression network by Weighted gene co-expression network analysis (WGCNA). Gene ontology (GO) as well as Kyoto Encyclopedia of Genes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Similar to the aforementioned findings in lung cells [39], Pirin is strictly regulated by NRF2 in pancreas cancer cells [82]. Moreover, high Pirin levels are associated with a reduced survival probability in cholangiocarcinoma patients, suggesting that Pirin is a plausible prognostic biomarker [83].…”
Section: Head and Neck And Gastrointestinal Cancerssupporting
confidence: 66%
“…Similar to the aforementioned findings in lung cells [39], Pirin is strictly regulated by NRF2 in pancreas cancer cells [82]. Moreover, high Pirin levels are associated with a reduced survival probability in cholangiocarcinoma patients, suggesting that Pirin is a plausible prognostic biomarker [83].…”
Section: Head and Neck And Gastrointestinal Cancerssupporting
confidence: 66%
“…Additionally, it was also documented that the inhibition of the hedgehog signaling pathway, a potential therapeutic target for human cholangiocarcinoma, attenuated the progression of carcinogenesis in vitro and subsequently increased the necrosis rate of cholangiocarcinoma [ 17 , 18 ]. Retinol metabolism has been less studied in cholangiocarcinoma, but there is literature suggesting that retinol metabolism is a key pathway in the development of cholangiocarcinoma [ 19 ]. Moreover, diabetes is associated with an increased risk of ICC, showing similar etiologies [ 20 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…IGF2 has been elucidated to be associated with retinol metabolism [30]. Furthermore, Liu et al observed that retinol metabolism was implicated in cholangiocarcinoma development [19].…”
Section: Discussionmentioning
confidence: 99%
“…The PRRG4 gene can help in the autistic symptoms of WAGR (Wilm's tumor, Aniridia, genitourinary malformations, and mental retardation) syndrome 33 . In addition, Liu et al identified proline rich and Gla domain 4 (PRRG4) as a potential prognostic marker in cholangiocarcinoma (CCA) 34 . Further study revealed that depletion of receptor expressing enhancing protein 5 (REEP5) significantly reduced growth and invasion in lung cancer 35 .…”
Section: Discussionmentioning
confidence: 99%